Factors Affecting Work Performance Efficiency of Personnel in the Territorial Defense Volunteer Corps Command, Kanchanaburi Province: Factors Affecting Work Performance Efficiency of Personnel in the Territorial Defense Volunteer Corps Command, Kanchanaburi Province - Tanyong, Panita; Phosing, Phakdee; Kenaphum, Sanya (RATANABUTH JOURNAL, 2026)
This study aimed to: (1) examine the level of operational efficiency among personnel of the Kanchanaburi Provincial Territorial Defense Volunteers Command; (2) identify the factors influencing their operational efficiency; and (3) propose recommendations regarding factors affecting such efficiency. This research employed a quantitative approach. The sample consisted of 171 personnel from the Kanchanaburi Provincial Territorial Defense Volunteers Command. Data were collected using a structured questionnaire and analyzed through descriptive statistics and multiple regression analysis. The findings revealed that: (1) the overall level of operational efficiency among personnel was at a high level; (2) the factors that significantly influenced operational efficiency at the .05 level were compensation, volunteerism, and organizational leadership, which together explained 61.50% of the variance in operational efficiency; and (3) recommendations for enhancing operational efficiency should focus on five key areas: strengthening morale, developing participatory leadership, establishing clear and actionable policies, fostering a culture of volunteerism within the organization, and improving compensation systems to ensure fairness and appropriateness.